Impact of Transcranial Doppler Ultrasound on Logistics and Outcomes in Stroke Thrombolysis: Results From the SITS-ISTR. Issue 7 (July 2018) - Mazya, Michael V.; Ahmed, Niaz; Azevedo, Elsa; Davalos, Antoni; Dorado, Laura; Karlinski, Michal; Lorenzano, Svetlana; Neumann, Jiří; Toni, Danilo; Moreira, Tiago P.
Abstract : Background and Purpose—: Diagnostic transcranial Doppler ultrasound (TCD) is commonly used in patients with acute stroke before or during treatment with intravenous thrombolysis (IVT). We aimed to assess how much TCD delays IVT initiation and whether TCD influences outcomes. Methods—: We analyzed data from the SITS-ISTR (Safe Implementation of Thrombolysis in Stroke–International Stroke Thrombolysis Register) collected from December 2002 to December 2011. Outcomes were door-to-needle time, symptomatic intracerebral hemorrhage, functional outcome per the modified Rankin Scale, and mortality at 3 months. Results—: In hospitals performing any TCD pre-IVT, 1701 of 11 265 patients (15%) had TCD before IVT initiation. Door-to-needle time was higher in patients with pre-IVT TCD (74 versus 60 minutes; P <0.001). At hospitals performing any TCD during IVT infusion, of 9044 patients with IVT, 747 were examined with TCD during IVT. No treatment delay was seen with TCD during IVT. After multivariate adjustment, TCD during IVT was independently associated with modestly increased excellent functional outcome (modified Rankin Scale, 0–1; adjusted odds ratio, 1.28; 95% confidence interval, 1.06–1.55; P =0.012) and lower mortality (adjusted odds ratio, 0.73; 95% confidence interval, 0.55–0.95; P =0.022). Conclusions—: We recommend that TCD, if performed, should be done during IVT infusion, to avoid treatment delay. The association of hyperacute TCD with beneficial outcomes suggests potential impact on patient management, which warrants further study. Abstract : Supplemental Digital Content is available in the text.